2011
DOI: 10.1175/jas-d-11-045.1
|View full text |Cite
|
Sign up to set email alerts
|

El Niño–Southern Oscillation in Tropical and Midlatitude Column Ozone

Abstract: The impacts of El Niñ o-Southern Oscillation (ENSO) on the tropical total column ozone, the tropical tropopause pressure, and the 3.5-yr ozone signal in the midlatitude total column ozone were examined using the Goddard Earth Observing System Chemistry-Climate Model (GEOS CCM). Observed monthly mean sea surface temperature and sea ice between 1951 and 2004 were used as boundary conditions for the model. Since the model includes no solar cycle, quasi-biennial oscillation, or volcanic forcing, the ENSO signal wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
(30 reference statements)
1
11
0
2
Order By: Relevance
“…Tung and Yang (1988) gave an analytic estimate of the TOC change as a function of change in tropopause height: TOC decreases by ;7% for each 0.5-km increase in the height of the tropopause. In the present study, TOC changes accompanied by an change in tropopause pressure at a rate of 1 DU hPa 21 , on the same order of magnitude as that estimated by Wang et al (2011) and Tung and Yang (1988). In addition, the patterns and magnitude of thermal tropopause height differences between El Niño and La Niña events in reanalysis are pretty similar to those in WACCM (Figs.…”
Section: How Enso Affects Midlatitude Ozonesupporting
confidence: 82%
See 2 more Smart Citations
“…Tung and Yang (1988) gave an analytic estimate of the TOC change as a function of change in tropopause height: TOC decreases by ;7% for each 0.5-km increase in the height of the tropopause. In the present study, TOC changes accompanied by an change in tropopause pressure at a rate of 1 DU hPa 21 , on the same order of magnitude as that estimated by Wang et al (2011) and Tung and Yang (1988). In addition, the patterns and magnitude of thermal tropopause height differences between El Niño and La Niña events in reanalysis are pretty similar to those in WACCM (Figs.…”
Section: How Enso Affects Midlatitude Ozonesupporting
confidence: 82%
“…2): negative height anomalies correspond to positive TOC anomalies and vice versa for positive height anomalies. Wang et al (2011) reported that the regression coefficient of tropopause pressure on the TOC simulated by the Goddard Earth Observing System-Chemistry (GEOS-Chem) model is 0.71 DU hPa 21 during ENSO events. Tung and Yang (1988) gave an analytic estimate of the TOC change as a function of change in tropopause height: TOC decreases by ;7% for each 0.5-km increase in the height of the tropopause.…”
Section: How Enso Affects Midlatitude Ozonementioning
confidence: 99%
See 1 more Smart Citation
“…The typical turnover time for the BDC is 1-2 years. While the BDC may play a role in the case of ENSO-related changes in polar O 3 [Soukharev and Hood, 2006;Wang et al, 2011], its effects on the observed intraseasonal variability, if any, have not be studied quantitatively. Global dynamical effects with different time scales ranging from daily to seasonal may also play a role in the teleconnection [Hudson et al, 2003;Garfinkel et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…To account for the SAM we apply the SAM index based on the UK's Met Office database (Marshall, 2003). A correlation between Antarctic stratospheric ozone depletion and the SAM index has been seen in observations Arblaster and Meehl, 2006;Wang et al, 2011; and references therein) and models (Perlwitz et al, 2008;Son et al, 2008;Thompson et al, 2011). The largest variability in the Antarctic stratosphere associated with the SAM signal is observed in the September-December period (Fogt et al, 2009).…”
Section: Proxy Data Setsmentioning
confidence: 99%